Selective Retinoic Acid Receptor γ Antagonist 7C is a Potent Enhancer of BMP-Induced Ectopic Endochondral Bone Formation - Tateiwa, Daisuke; Kaito, Takashi; Hashimoto, Kunihiko; Okada, Rintaro; Kodama, Joe; Kushioka, Junichi; Bal, Zeynep; Tsukazaki, Hiroyuki; Nakagawa, Shinichi; Ukon, Yuichiro; Hirai, Hiromasa; Tian, Hongying; et al. (Frontiers in Cell and Developmental Biology, 2022)
Bone morphogenetic proteins (BMPs) have been clinically applied for induction of bone formation in musculoskeletal disorders such as critical-sized bone defects, nonunions, and spinal fusion surgeries. However, the use of supraphysiological doses of BMP caused adverse events, which were sometimes life-threatening. Therefore, safer treatment strategies for bone regeneration have been sought for decades. Systemic administration of a potent selective antagonist of retinoic acid nuclear receptor gamma (RARγ) (7C) stimulated BMP-induced ectopic bone formation. In this study, we developed 7C-loaded poly lactic nanoparticles (7C-NPs) and examined whether local application of 7C enhances BMP-induced bone regeneration. The collagen sponge discs that absorbed recombinant human (rh) BMP-2 were implanted into the dorsal fascia of young adult mice to induce ectopic bone. The combination of rhBMP-2 and 7C-NP markedly increased the total bone volume and thickness of the bone shell of the ectopic bone in a dose dependent manner compared to those with rhBMP-2 only. 7C stimulated sulfated proteoglycan production, expression of chondrogenic marker genes, and Sox9 reporter activity in both chondrogenic cells and MSCs. The findings suggest that selective RARγ antagonist 7C or the related compounds potentiate the bone inductive ability of rhBMP-2, as well as support any future research to improve the BMP-2 based bone regeneration procedures in a safe and efficient manner.